2020
DOI: 10.3390/ma13122709
|View full text |Cite
|
Sign up to set email alerts
|

Using Environmental Simulations to Test the Release of Hazardous Substances from Polymer-Based Products: Are Realism and Pragmatism Mutually Exclusive Objectives?

Abstract: The potential release of hazardous substances from polymer-based products is currently in the focus of environmental policy. Environmental simulations are applied to expose such products to selected aging conditions and to investigate release processes. Commonly applied aging exposure types such as solar and UV radiation in combination with water contact, corrosive gases, and soil contact as well as expected general effects on polymers and additional ingredients of polymer-based products are described. The rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…However, it could be used to vary single factors and better understand outdoor leaching behavior. In [ 46 ], a 24 h weathering cycle for the leaching of organic materials is introduced by Bandow et al As inorganic constituents are partially incorporated into the leached material and generally show another emission behavior than organics, an adaption on concrete would have to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…However, it could be used to vary single factors and better understand outdoor leaching behavior. In [ 46 ], a 24 h weathering cycle for the leaching of organic materials is introduced by Bandow et al As inorganic constituents are partially incorporated into the leached material and generally show another emission behavior than organics, an adaption on concrete would have to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term stability of geotextiles is usually investigated with relation to mechanical stability, which must fulfill certain requirements after aging. Various methodologies are available (e.g., elevated temperatures or increase in oxygen pressure) to accelerate aging in the laboratory [ 4 ]. Mechanical properties, such as tensile strength, investigation of chemical oxidation reactions by infrared spectroscopy, and the residual content of stabilizers are typical parameters tested on aged samples [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This method might not cover the worst case leaching conditions and therefore underestimates the actual emissions. Hecht and Schoknecht et al for example showed that not only the duration of water contact, but also the transport during drying phases determines the emissions [24,29], the DSLT does not achieve realistic exposure conditions [30]. Still it is desirable to find or develop a horizontal and therefore universally applicable and easily adaptable concept for the assessment of the environmental compatibility of irrigated construction components.…”
Section: Introductionmentioning
confidence: 99%